TINDAK PIDANA DENGAN SENGAJA DAN DIRENCANAKAN LEBIH DAHULU MENGHILANGKAN NYAWA ORANG LAIN - Muhammad Ilhamsyah Putra; Vientje Ratna Multiwijaya (Fakultas Hukum Universitas Trisakti, 2023)
Humica Tambunan, the defendant, and Muhammad Iqbal, the victim, committed the premeditated murder offense. After becoming enraged with the victim for using his money, the defendant hit him in the back of the head with a piece of wood from his chamber. The victim was then crushed in the face by a mattress till he died. The issue is whether the defendant's intentional and premeditated killing of another person satisfies the requirements of Article 338 of the Criminal Code, and whether or not a 9-year prison sentence was properly imposed by the judge in light of this conviction. The normative research approach is descriptive, gathering evidence through literature analysis, and analyzing qualitatively by coming to deductive conclusions. Research findings and discussion; with the element of premeditation, a term of imprisonment for 20 years under Article 340 of the Criminal Code is more suitable because it was done on purpose and with advance planning. Conclusion of the study; 20-year prison sentence for the offender in violation of Article 340 of the Criminal Code.